Allergic Manifestation in Paediatric Patients with Primary Immunodeficiency Diseases (Journal of Medical Science, 2020)
Introduction. Primary immunodeficiency diseases (PID) are a diverse group of rare genetic disorders that affect the development and/or function of the immune system. Affected individuals are predisposed to an increased rate and severity of infections, allergy, autoimmunity and malignancy. Primary immunodeficiency diseases are considered rare; physicians and general practitioners have little knowledge about the clinical presentation, diagnostic approach and health impact of PID. Many PID patients have a clinical history in favour of allergic diseases. Nevertheless, in these patients, the importance and prevalence of atopic disorders have not been completely explained. Aim. The aim of this study was to evaluate atopic presentations, including atopic dermatitis, allergic rhinitis and asthma in a group of PID patients under the care of our clinic. Material and Methods. Fifty-seven pediatric patients with PID primary immunodeficiency diseases were enrolled from March 2018 to April 2019. Serum IgE levels were measured. Information regarding the patient’s history of allergic diseases, including asthma, allergic rhinitis and atopic dermatitis were analysed. Results and Conclusions. Confirmed allergy/asthma was found in 40 patients (70%). Thirty-eight patients (66.7%) had a diagnosis of asthma, 7 patients (12.3%) of allergic rhinitis and 13 (22.8%) of atopic dermatitis. Serum IgE total level was elevated in 12 patients (21%).